Lamotrigine as monotherapy in clinical practice: efficacy of various dosages in epilepsy. Issue 3 (10th February 2016) - Warshavsky, Anton; Eilam, Anda; Gilad, Ronit
Abstract: Objectives/Aims: The study was designed to evaluate the optimal dosage of lamotrigine, as monotherapy, in the treatment of adults suffering from complex partial seizures with or without secondary generalization in everyday clinical practice. Materials and Methods: The ones used in this study was the collection of the data of all adult patients treated with lamotrigine, retrospectively. The dosage and efficacy of treatment were evaluated along with side effects and retention rate. Results: They showed that, out of 188 patients, 77% continued lamotrigine treatment; the mean effective dose was 250 mg or higher of lamotrigine, and the results more pronounced in older patients (age above 30 years) and those with a longer disease duration (5 years and more). Conclusion: It may be appropriate to reach a daily lamotrigine dose above 250 mg in adult patients suffering from epilepsy for more than 5 years using lamotrigine as monotherapy. Abstract : To conclude, it may be appropriate to reach a daily LTG dose above 200 mg in adult patients suffering from epilepsy for more than 5 years and are treated with LTG as monotherapy